Boosting Tourism’s Contribution to Growth and Development: Analysis of Evidence - Banerjee, Onil (2017)
In this study we develop an evidence-based tool to help to guide policy and investment choices, to maximize developmental returns from tourism. Specifically, we develop a tourism-extended social accounting matrix and computable general equilibrium and microsimulation models customized for tourism investment analysis. To demonstrate the approach, we develop these data structures for Belize, at both national and regional levels. The framework developed herein can be used to quantify the direct and indirect, and shortand long-run impacts of tourism investments. Anticipating application of the approach to tourism investment analysis in the Central American Region, we provide a stock take of the availability of data to develop a similar suite of models for other countries in the region.